The current state of artificial intelligence-augmented digitized neurocognitive screening test - Sirilertmekasakul, Chananchida; Rattanawong, Wanakorn; Gongvatana, Assawin; Srikiatkhachorn, Anan (Frontiers in Human Neuroscience, 2023)
The cognitive screening test is a brief cognitive examination that could be easily performed in a clinical setting. However, one of the main drawbacks of this test was that there was only a paper-based version available, which is restricting the test to be manually administered and graded by medical personnel at the health centers only. The main solution to these problems was to develop a potential remote assessment for screening individuals with cognitive impairment. Currently, multiple studies have been adopting artificial intelligence (AI) technology into these tests, evolving the conventional paper-based neurocognitive test into a digitized AI-assisted neurocognitive test. These studies provided credible evidence of the potential of AI-augmented cognitive screening tests to be better and provided the framework for future studies to further improve the implementation of AI technology in the cognitive screening test. The objective of this review article is to discuss different types of AI used in digitized cognitive screening tests and their advantages and disadvantages.